دراسة إحصائية لواقع السياحة في سورية - الرفاعي عبد الهادي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
مع بداية الثورة الصناعية الكبرى بدأت السياحة تلفت انتباه المسؤولين, و تسترعي اهتمام ونظر الباحثين, نظراً لآثارها الاقتصادية الهامة، ولما توفره من زيادة في الدخل القومي يسهم في التنمية الاجتماعية والاقتصادية. فالإنفاق الذي يكون عادة لقاء خدمات يحصل عليها السائح أو مقابل سلع يشتريها, يشكل مورداً اقتصادياً للمنطقة التي تستقطب السياح و مجالاً لتشغيل الأيدي العاملة، ولذلك برز المفهوم الاقتصادي للسياحة وما يمكن أن تلعبه هذه السياحة من دور في التطور الاقتصادي للبلدان . إن للسياحة مقومات عديدة, قد لا يتسنى لكل الدول أن تمتلكها, وهناك بعض الدول التي تمتلك تلك المقومات ولكنها لا تحسن استخدامها, وسورية رغم أنها تصنف من دول العالم الثالث الزراعية, إلا أنها تمتلك مقومات سياحية كبيرة غير أنها لا تحسن استثمارها, رغم المحاولات الكثيرة وغير المنظمة التي تقوم بها لاستثمار هذا القطاع الاقتصادي الهام. و هذا ما دفعنا إلى البحث في هذا المجال للوقوف على التطورات التي حدثت في مجال السياحة من خلال رصد الواقع السياحي في سورية، للوقوف على أهم التغيرات التي حدثت في هذا القطاع، وقد تبين لنا أنه حتى الآن لا توجد صناعة سياحية في سورية، وأن السياحة ما تزال تعيش حالة من الفوضى والعشوائية وانعدام التخطيط. With the beginning of the great industrial revolution tourism began to attract the attention of the authorities because of its important economical effects, and because it provides an increase in the national income that helps the social and economic building. Spending money for services the tourist has, or for goods he buys, is considered an economical source for the area that attracts the tourists and an creates jobs. For this reason, the economical concept of tourism and its role in the economical development for countries arose. Tourism has many characteristics, but many countries may not have them, whereas other countries have them but can’t use them well. Syria, despite its classification as an agricultural country in the Third World, has many tourist factors but doesn’t utilize them properly, in spite of the several unorganized attempts to invest in this important economical sector . This study highlights the developments which took place in Syria in the field of tourism to have an idea about the major changes that took place in this sector; we found out that there was neither real tourism industry, nor effective tourism investment. Tourism in Syria is still chaotic and purposeless, and unplanned.